TCT (Trash Can Talk) Berbasis Arduino dengan Sistem Solar Cell untuk Sarana Pembelajaran Anak - Afriliana, Ida; Setiawan, Andi; Taftazani, Andre Juan; Navita, Heki Rahayu; Bukhari, Imam (Universitas Islam Negeri Walisongo Semarang, 2021)
Sometimes, some people do not throw trash in their place because they are lazy, so it happens to children. Many children prefer to throw trash at anywhere and become one of the problems in the school or community environment. . This is a bad habit because there is no awareness to keep the environment clean. This research is to produce an Arduino-based TCT (Trash Can Talk) rubbish bin with a solar cell system for learning tools for orderly behavior of garbage disposal in children. TCT was made using an arduino uno R3 microcontroller, a PIR sensor to detect the presence of children so that the trash can emit 2 sounds from the DF mini mp3 player through the speaker alternately to attract the attention of children and